Mass distributions in disk galaxies. Issue Volume 11:Issue S321(2015) (21st March 2017) - Martinsson, Thomas; Verheijen, Marc; Bershady, Matthew; Westfall, Kyle; Andersen, David; Swaters, Rob
Abstract: We present results on luminous and dark matter mass distributions in disk galaxies from the DiskMass Survey. As expected for normal disk galaxies, stars dominate the baryonic mass budget in the inner region of the disk; however, at about four optical scale lengths ( hR ) the atomic gas starts to become the dominant contributor. Unexpectedly, we find the total baryon to dark-matter fraction within a galaxy stays nearly constant with radius from 1 hR out to at least 6 hR, with a baryon fraction of 15–50% among galaxies. On average, only one third of the mass within 2.2 hR in a disk galaxy is baryonic and these baryons appear to have had only a minor effect on the distribution of the dark matter.